Dampak Psikis dan Manifestasi PTSD akibat Trauma Kekerasan Masa Kecil - Qumi Matus Soibeh; Vinny Pratisha Ramadhani (Edukasi Elita : Jurnal Inovasi Pendidikan, 2026)
Psychological Impact and Manifestations of PTSD Due to Childhood Violence Trauma represent a complex intersection of developmental disruption and chronic emotional distress. Children exposed to such violence often internalize the trauma, leading to profound shifts in their mental health that manifest as persistent hypervigilance, emotional numbing, and intrusive memories that disrupt their daily functioning. Beyond immediate fear, these manifestations involve structural changes in the brain, such as an overactive amygdala and a reduced volume of the hippocampus and prefrontal cortex, which impair a child's ability to regulate emotions and process information. Behaviorally, this often translates into externalizing symptoms like aggression and irritability, or internalizing reactions such as social withdrawal, dissociation, and "foreshortened future"—a belief that they will not live a long or normal life. If left unaddressed, these psychological scars can evolve into chronic anxiety, depression, and severe difficulties in forming healthy interpersonal relationships, creating a cycle of vulnerability that persists well into adulthood and impacts their overall quality of life.